Nutrient Digestibility of Diets with Different Levels of Dried Distillers Cassava with Solubles (DDCS) in Growing and Finishing Pigs - Pholchaiyaphum, Wanvisa; Wongtangtintharn, Sawitree; Uriyapongson, Suthipong; Khammeng, Terdsak (Pakistan Journal of Nutrition, 2018)
Background and Objectives: This study was designed to evaluate the effects of supplementing 4 levels of dried distillers cassava with solubles (DDCS) on nutrient digestibility in growing and finishing pigs. Materials and Methods: Fifteen female crossbred pigs were allocated to 5 treatments and 3 replicates with a completely randomized design (CRD). Each pig was kept in a solitary cage and received the following diets: control diet with no added DDCS; control diet supplemented with 5, 10, 15 and 20% DDCS for growing pigs and control diet supplemented with 10, 20, 30 and 40% DDCS for finishing pigs. Results: The chemical components of DDCS comprised dry matter (DM, 91.63%), crude protein (CP, 5.64%), crude fat or ether extract (EE, 1.28%), crude fibre (CF, 26.78%), ash (11.71%), calcium (Ca, 0.89%), phosphorus (P, 0.43%) and gross energy (GE, 3,434 kcal kg–1). The nutrient digestibility of DM, CP and ash in the diets supplemented with DDCS in both the growing and finishing periods decreased as the level of DDCS increased (linear effect, p<0.05), whereas the digestibility of EE or fat and CF increased (linear and quadratic effect, p<0.05) when the DDCS content increased. Conclusion: The inclusion of graded levels of 5, 10, 15 and 20% DDCS in growing pig diets and 10, 20, 30 and 40% DDCS in finishing pig diets decreased the nutrient digestibility of DM, CP and ash but increased the digestibility of EE and CF as the levels of DDCS increased.